Biotransformation of asiaticoside using Aspergillus niger and pharmaceutical properties of its transformed product - Omar, Muhammad Nor; Alfarra, Helmi Yousif; Arief Ichwan, Solachuddin Jauhari (2016)
Asiaticoside, is one of the bioactive constituents in Centella asiatica, has been reported to have wound healing properties. Biotransformation was extensively used to create useful metabolites from various natural products and as an alternative to chemical synthesis for the preparation of pharmacologically active compounds. The purpose of this study is to investigate the effects of asiaticoside and its transformed product on wound healing activities. Microbial transformation of asiaticoside using Aspergillus niger was carried out to produce an asiaticoside transformed product which has pharmaceutical properties. The wound healing activities of asiaticoside and its transformed product were investigated and their effects on TGFβ1 and TIMP1 gene expression were examined in order to understand their mode of action on healing. Asiaticoside and its transformed product were also used in the cell proliferation and wound healing experiments using human keratinocytes. Results of in vitro study showed that asiaticoside concentrations between 7.5 and 120 μg/ml gave higher value of cell proliferation than the negative control, prompting cell proliferation improvement. On the other hand, it was found that the transformed product concentrations between 0.058 and 3.75 μg/ml exhibited the higher cell viability values. In wound healing assays analysis, it was shown that there were significant differences on wound closure in comparison with the negative control (P<0.05). Analysis showed that both asiaticoside and the transformed product increased the expression of TGFβ1 and TIMP1 respectively. However, the transformed product was more effective than asiaticoside on the expression of TGFβ1 and TIMP1 respectively. It was observed that the asiaticoside-transformed product showed a faster migration and healing speed under macroscopic observation.